Chapter 2 Conscious and Unconscious Qualities Conceptual Relations between Phenomenality, What-It's-Likeness, and Consciousness - Polák, Michal (Taylor & Francis, 2024)
The chapter considers the possibility of separating phenomenality from consciousness. Perhaps the most serious consequence of this move is that it encourages the concept of unconscious qualities. This idea is not entirely new (Cf. Rosenthal 2010; Marvan and Polák 2017 where they call it dual model), but its wider acceptance is confronted with a lack of clarity about the relationships between fundamental concepts involved in the unconscious qualities framework. The main aim is to briefly introduce the dual framework, the standard orthodoxy (no-unconscious-qualities view), and further elaborate on particular conceptual issues arising in connection with the involvement of the three basic concepts: phenomenality, what-it's-likeness (WIL), and consciousness. I will thus attempt to reconsider three types of conceptual relations: 1) phenomenality to WIL, 2) consciousness to phenomenality, and 3) consciousness to WIL. The chapter will address, among other things, two pressing issues that the dual framework entails, namely the status of consciousness and the distinction between unconscious qualities and WIL.